Thrombolysis in Pulmonary Embolism - Jerjes-Sánchez, Carlos (Springer International Publishing : Imprint: Springer, 2015)
This book provides an up-to-date review of the use of thrombolytic therapy in the treatment of acute pulmonary embolism. It discusses the mechanisms of thrombosis; pharmacokinetics and pharmacodynamics of the most commonly used fibrinolytics; evidence-based results from multicenter control trials in which thrombolytic treatment was administered; criteria by which pulmonary embolism patients requiring thrombolysis are identified; and the use of thrombolytic therapy in special situations such as in in-transit thrombus and pregnancy. Focusing on peripheral intravenous thrombolysis, which can be performed safely and effectively in emergency departments, hospital wards, and intensive critical care units in tertiary and community hospitals, Thrombolysis in Pulmonary Embolism is a valuable resource for cardiologists, pulmonologists, and internists.    .